Impressions of wildlife in Canada in the spring of 1958 - Eltringham, S K (Wildfowl, 1959)
Arrangements were made by the Nature Conservancy for two members of the Wildfowl Trust scientific staff to visit Canada in the spring and summer of 1958 to observe the techniques of aerial surveys which are carried out by the U. S. Fish and Wildlife Service at that time of year. It is not my intention to give a detailed report of the aerial survey techniques--some attempt at that has been made elsewhere in this Report--but perhaps a few of the many impressions gained of Canada and its wildlife may be of interest.